2016
DOI: 10.21070/pedagogia.v5i2.259
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar

Abstract: PENDAHULUANProses pembelajaran Ilmu Pengetahuan Alam menekankan pada pemberian pengalaman langsung untuk mengembangkan kompetensi agar menjelajahi dan memahami alam sekitar secara ilmiah. Pembelajaran Ilmu Pengetahuan Alam sebaiknya dilaksanakan secara inkuiri ilmiah (scientific inquiry) untuk menumbuhkan kemampuan berpikir kritis, bekerja dan bersikap ilmiah serta mengkomunikasikannya sebagai aspek penting kecakapan hidup. AbstractThis research aims to determine the application of guided inquiry learning mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
1
3
0
15
Order By: Relevance
“…The low learning outcomes in the experimental class II due to the learning process which still applying direct learning model (Direct Instruction), in which the teacher is still the center of learning by demonstrating practical activities, consequently most students become bored in learning because they cannot actively find concepts through experimental activities simple (practicum). This is in line with the research conducted by Wulandari (2016) which concluded that learning with the Guided Inquiry model on the Colligative Characteristics of the Solution can improve the learning outcomes of TKJ-I students in Way Kanan High School by 88.89% with complete and very good categories. This is because in Guided Inquiry learning students are required to be active to think critically, find problems with reasoning, and develop knowledge independently so that it will be more embedded in the mind and more remembered by students.…”
Section: Discussionsupporting
confidence: 90%
“…The low learning outcomes in the experimental class II due to the learning process which still applying direct learning model (Direct Instruction), in which the teacher is still the center of learning by demonstrating practical activities, consequently most students become bored in learning because they cannot actively find concepts through experimental activities simple (practicum). This is in line with the research conducted by Wulandari (2016) which concluded that learning with the Guided Inquiry model on the Colligative Characteristics of the Solution can improve the learning outcomes of TKJ-I students in Way Kanan High School by 88.89% with complete and very good categories. This is because in Guided Inquiry learning students are required to be active to think critically, find problems with reasoning, and develop knowledge independently so that it will be more embedded in the mind and more remembered by students.…”
Section: Discussionsupporting
confidence: 90%
“…Dalam penelitian ini berpikir kritis pada kelas eksperimen lebih baik daripada kelas kontrol, karena kelas uji coba diterapkan model pembelajaran inkuiri terbimbing berbantuan media power point yang memungkinkan siswa bisa bertukar ide-ide, bertukar pikiran, dan saling mengemukakan pendapat, sehingga berpikir kritis siswa bisa meningkat. Hal tersebut ditunjang dari opini Wulandari (2016) Berdasarkan hasil analisis dan kajian penelitian yang relevan, penggunaan metode inkuiri terbimbing berbantuan media power point memberikan kontribusi yang baik bagi keterampilan berpikir kritis siswa dalam mata pelajaran di MA Al-Aziziyah Putri. Dengan bermetodekan inkuiri terbimbing, siswa dapat berperan aktif, belajar secara mandiri untuk memecahkan suatu masalah maka keterampilan berpikiran kritis siswa dapat meningkat.…”
Section: Pembahasanunclassified
“…Learning science in elementary schools is one of the subjects that has a high level of difficulty (Laeli et al, 2020). Furthermore, (Wulandari, 2016) said that learning science can make students think critically. Thus, science learning in elementary schools is taught at a high level of conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%